1998
DOI: 10.1254/jjp.78.199
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Protection by S-Allylmercaptocysteine Against Acetaminophen-Induced Liver Injury in Mice

Abstract: S-Allylmercaptocysteine (SAMC), one of the water-soluble organosulfur compounds in ethanol extracts of garlic (Allium sativum L.), has been shown to protect mice against acetaminophen (APAP)-induced liver injury. In this study, we examined the mechanisms underlying this hepatoprotection. SAMC (100 mg/kg, p.o.) given 2 and 24 hr before APAP administration (500 mg/kg, p.o.) suppressed the plasma alanine aminotransferase activity increases 3 to 12 hr after APAP administration significantly. The hepatic reduced gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…These characteristic components are not contained in the raw garlic, and are made from gamma-glutamyl-SAC (GSAC), gamma-glutamyl-SMC (GSMC), alliin or methiin after extracted/aged on raw garlic for a long period. They have been reported to possess anti-oxidative [14][15][16], cancer preventive [17][18][19] and hepatoprotective properties [20]. The anti-fatigue effect of garlic differs according to the processing method employed, and it has been demonstrated that AGE is one of the processed products that has the most desirable effects [21,22].…”
Section: Garlicmentioning
confidence: 99%
“…These characteristic components are not contained in the raw garlic, and are made from gamma-glutamyl-SAC (GSAC), gamma-glutamyl-SMC (GSMC), alliin or methiin after extracted/aged on raw garlic for a long period. They have been reported to possess anti-oxidative [14][15][16], cancer preventive [17][18][19] and hepatoprotective properties [20]. The anti-fatigue effect of garlic differs according to the processing method employed, and it has been demonstrated that AGE is one of the processed products that has the most desirable effects [21,22].…”
Section: Garlicmentioning
confidence: 99%
“…Specifically, we studied liver and kidney because garlic compounds undergo hepatic metabolism and are excreted in the urine (15), and we assessed the stomach epithelium due to its direct exposure to concentrated S-allylmercaptocysteine. In fact, previous animal studies showed that 200 mg/kg S-allylmercaptocysteine actually protected against toxin-induced liver damage, with similar efficacy to human hepatoprotective drug N-acetylcysteine (27). It is noteworthy that N-acetylcysteine has a similar cysteinebased chemical structure to S-allylmercaptocysteine and is administered routinely to humans in oral doses of 540 mg/kg/ d, supporting the clinical relevance of the 300 mg/kg/d S-allylmercaptocysteine dose we administered to our mice.…”
Section: Discussionmentioning
confidence: 94%
“…To exclude serious toxicity, we screened for the presence of organ pathology in S-allylmercaptocysteine -treated mice using a 50% higher dose (300 mg/kg/d) than the maximum previously described (27). After treating for 30 days, no anatomic abnormalities or signs of inflammation, necrosis, or hemorrhage were observed at postmortem evaluations.…”
Section: Resultsmentioning
confidence: 99%
“…A relatively lower degree of hepatic damage in the CoQ10 group is indicative of the hepatoprotective nature of CoQ10. While there is no direct evidence of the hepatoprotective effect of CoQ10, it has been reported that maintenance of the normal level of CoQ9H2 in the S-allylmercaptocysteine pretreatment group may suppress acetaminophen-induced liver injury (Sumioka et al, 1998).…”
Section: Discussionmentioning
confidence: 99%